Bipedicle Dermis Fat Graft for Orbital Volume Augmentation and Repair of Lower Eyelid Retraction in an Anophthalmic Socket With Prior Orbital Implant Placement. Issue 2 (March 2019) - Godfrey, Kyle J.; Tooley, Andrea A.; Kazim, Michael
Abstract : Buphthalmos can create treatment challenges for socket rehabilitation following enucleation due to compression atrophy and mechanical stretching of adnexal tissues. The authors report a case demonstrating a surgical technique for simultaneous volume augmentation of the anophthalmic socket, expansion of the conjunctival fornix, and repair of lower eyelid retraction in a patient with history of buphthalmos and a previously placed 22 mm orbital implant at the time of enucleation. The authors utilized a single-stage, bipedicle dermis fat graft. Postoperatively, the patient demonstrated improvement in lower eyelid position, lower eyelid volume, improved prosthesis fit, improved three-dimensional projection of the ocular prosthesis, and an improvement in the superior sulcus deformity. Bipedicle dermis fat grafts are an option for surgical rehabilitation of the anophthalmic socket when orbital volume deficiency, conjunctival fornix contracture, and eyelid retraction are present and an adequately sized orbital implant has previously been placed. Abstract : The authors report a case demonstrating a surgical technique for simultaneous volume augmentation of the anophthalmic socket and lower eyelid, expansion of the conjunctival fornix, and repair of lower eyelid retraction utilizing a bipedicle dermis fat graft.